Computational Approaches to Sentence Completion - Platt, John; Zweig, Geoffrey; Meek, Chris; Burges, Chris J.C.; Liu, Qiang (ACL 2012, 2012)
This paper studies the problem of sentence level semantic coherence by answering SATstyle sentence completion questions. These questions test the ability of algorithms to distinguish sense from nonsense based on a variety of sentence-level phenomena. We tackle the problem with two approaches: methods that use local lexical information, such as the n-grams of a classical language model; and methods that evaluate global coherence, such as latent semantic analysis. We evaluate these methods on a suite of practice SAT questions, and on a recently released sentence completion task based on data taken from five Conan Doyle novels. We find that by fusing local and global information, we can exceed 50% on this task, and we suggest some avenues for further research.